2014
DOI: 10.1007/s10646-014-1213-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of chemical markers for the identification of farm escapees in feral mink populations

Abstract: Variations in the contaminant burden in feral and ranch mink, resulting from differences in their diet, may permit the identification of farm escapees. However, this is only possible in the case of contaminants that accumulate to significantly different levels in the two groups of animals. The main objective of this study was to identify chemical markers whose concentrations differ between feral and ranch mink, by analyzing the accumulation of 13 chemical elements in liver and kidney samples. Total mercury lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a Polish study, chemical markers such as Hg and Cu were used for the identification of first generation mink farm escapees [21]. Analyses of the accumulation of 13 chemical elements in liver and kidney samples from farmed and wild mink showed significant differences in the levels of Hg and Cu between the two groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Polish study, chemical markers such as Hg and Cu were used for the identification of first generation mink farm escapees [21]. Analyses of the accumulation of 13 chemical elements in liver and kidney samples from farmed and wild mink showed significant differences in the levels of Hg and Cu between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the accumulation of 13 chemical elements in liver and kidney samples from farmed and wild mink showed significant differences in the levels of Hg and Cu between the two groups. The total Hg levels were up to 15-fold higher in the kidney, and up to 7-fold higher in the liver of wild mink compared to farmed mink [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to compare the concentration of nickel in American mink in Iceland with the results obtained by other authors. Brzeziński et al (2014) reported an average content of this element in kidneys and livers of N. vison from Poland (Drawa National Park) of 0.29 and 0.27 mg × kg −1 dry weight, respectively. Ni concentration in livers of animals from the vicinity of Sudbury (Canada), home to the world's largest nickel smelting operation, ranges from 0.43 to 0.7 mg × kg −1 , while in kidneys it ranges from 0.5 to 0.74 mg × kg −1 (all values for wet weight; Wren et al 1988;von Schmalensee 2010;Parker & Capodagli 2011).…”
Section: Discussionmentioning
confidence: 99%